Penerapan Konsep Smart Environment Melalui Program Kampung Iklim Menuju Tanjungpinang Smart City (Studi kasus Kelurahan Tanjung Unggat Kecamatan Bukit Bestari) - Rizky Gunawan; Fitri Kurnianingsih; Ramadhani Setiawan (Pusat Riset dan Inovasi Nasional, 2023)
This research refers to the Decree of the Minister of Environment and Forestry of the Republic of Indonesia Number 19 of 2012 concerning the Implementation of the Climate Village Program as an alleviation of environmental problems and aligning the Tanjungpinang Mayor Regulation Number 84 of 2020 concerning the Tanjungpinang Smart City Master Plan (Tanjungpinang Master Plan Smart City). The theory in this study refers to Cohen's Theory namely Smart Buildings, Resource Management, and Sustainable Urban Planning. The conclusion of this study is that the Tanjung Unggat Village is capable of carrying out the Implementation of the Climate Village Program in accordance with the dimensions smart environment and designs that have been compiled through theory and the Tanjungpinang City Masterplan.